Challenges of Negotiating Sectoral Governance of Street Vending Sector in Harare Metropolitan, Zimbabwe - Njaya, Tavonga (Asian Journal of Economic Modelling, 2014)
Informal businesses have decorated the streets of Harare and have become an increasingly visible and disruptive locus of conflict between the government’s efforts to maintain public order on one hand and the citizens’ efforts to generate income on the other. This study sought to investigate the problems hindering the establishment of a stable governance framework of street vending sector in Harare in Zimbabwe. The study used qualitative approach.Data were collected through in-depth personal interviews, direct observations and document reviews. Semi-structured questionnaires were administered to 145 street vendors in Harare. The study revealed that the inability to achieve stable governance of street vending may be rooted in problems at the national, metropolitan and local levels. First, policy contradictions caused by conflicting political incentives at different levels of the state have made establishment of sectoral governance rather elusive. Second, at the metropolitan level, neoliberal by-laws and regulations continued to exclude street vendors from participating in the economic activities of the country. These by-laws have failed to adapt to the changing circumstances. Third, street vendors lacked formal association(s) that can coordinate strategies across different groups to achieve sectoral governance. The study provided an insight into an emerging research area that is characterised by a proliferation of a variety of types of street vendors in Harare. The study showed that while vending associations had been unsuccessful in their efforts to achieve sectoral governance, the new interest regime could offer novel strategies of action to achieve this goal.